2014
DOI: 10.1186/1478-811x-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and pancreatic cancer: molecular and functional interactions between S100A8, S100A9, NT-S100A8 and TGFβ1

Abstract: BackgroundIn order to gain further insight on the crosstalk between pancreatic cancer (PDAC) and stromal cells, we investigated interactions occurring between TGFβ1 and the inflammatory proteins S100A8, S100A9 and NT-S100A8, a PDAC-associated S100A8 derived peptide, in cell signaling, intracellular calcium (Cai2+) and epithelial to mesenchymal transition (EMT). NF-κB, Akt and mTOR pathways, Cai2+ and EMT were studied in well (Capan1 and BxPC3) and poorly differentiated (Panc1 and MiaPaCa2) cell lines.ResultsNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…When combined with S100A8, S100A9 constitutes the heterodimeric protein calprotectin (S100A8/9), which is expressed in nearly all cells, tissues and fluids in the human body . A recent study explored the relationship between pancreatic cancer, S100A9/A8 and transforming growth factor beta 1 (TGFβ1) concluded that the overexpression of S100A9/A8 by infiltrating inflammatory cells and the expressions is related to TGFβ1 in pancreatic ductal adenocarcinoma (PDAC) . Interleukin‐17 (IL‐17), a pro‐inflammatory cytokine mainly produced by T‐helper 17 (Th 17) cells, has been reported to play a crucial role in the development of an effective immune response .…”
Section: Introductionmentioning
confidence: 99%
“…When combined with S100A8, S100A9 constitutes the heterodimeric protein calprotectin (S100A8/9), which is expressed in nearly all cells, tissues and fluids in the human body . A recent study explored the relationship between pancreatic cancer, S100A9/A8 and transforming growth factor beta 1 (TGFβ1) concluded that the overexpression of S100A9/A8 by infiltrating inflammatory cells and the expressions is related to TGFβ1 in pancreatic ductal adenocarcinoma (PDAC) . Interleukin‐17 (IL‐17), a pro‐inflammatory cytokine mainly produced by T‐helper 17 (Th 17) cells, has been reported to play a crucial role in the development of an effective immune response .…”
Section: Introductionmentioning
confidence: 99%
“…Serum biomarkers, S100A8, S100A9, and CXCL4, were identified from GBM patients' serum by using surface‐enhanced laser desorption/ionization time‐of‐flight and liquid chromatography–MS/MS technologies (Popescu et al ., ). Their functions are correlated with acute inflammatory reactions to cancer cells (Basso et al ., ; Gebhardt et al ., ) and disease‐related cystic fibrosis (van Bon et al ., ; Schwartzkopff et al ., ). We applied a similar proteomic methodology and found that the level of the SAA1 protein in the plasma of patients with GBM was higher than that in the plasma of healthy people; this was confirmed through protein blot analysis conducted on different cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…These findings appear in disagreement with those of Levy and Hill [42], who demonstrated that SMAD4 silencing completely abolished TGFβ1 induced migration and this discrepancy might depend on differences between the cellular models and TGFβ1 dosages. We used low amounts of TGFβ1 (0.02 ng/mL) because they were comparable to those used by Yasutome et al [49], they were previously demonstrated by us to induce the epithelial to mesenchymal transition in BxPC3 [28] and they were consistent with the amount released by pancreatic tumor cells [50]. Although the low TGFβ1 dosage might be unable to induce Smad2/3 phosphorylation, never observed in our experimental conditions, a potential disruption in the TGFβ receptors might also be hypothesized [51].…”
Section: Discussionmentioning
confidence: 99%